Decoding the genome of Bacillus thuringiensis subsp. israelensis VCRC B668 to understand its mosquitocidal potential for biopesticide development - Jibi Lukose; A. Mathivanan; Bhavna Gupta; Sahadiya Mandodan; V. Abhisubesh; Kakhuangailiu Gangmei; Bhagyashree Bora; Aneha Kunnikuruvan; P. Hemaladkshmi; I. Geetha; S. Poopathi; R. Paramasivan (Brazilian Journal of Microbiology, 2026)

Streamflow prediction with machine learning: evaluating predictability across hydroclimatic regimes - Shivam Kumar Dwivedi; Geetha P; Bankaru-Swamy Soundharajan; S. Mohanasundaram (Hydrological Sciences Journal, 2026)

A rapid field–based protocol to assess the heavy metals bioindicator potential of Azolla pinnata in diverse wastewater systems - Arpita Kumari; Geetha P; Sivakumar S (Environmental Monitoring and Assessment, 2026)

Characterization of river-dredged material for sustainable reuse in road construction - Parvathi Geetha Sreekantan; Mariya Dayana P. J.; Anil Kumar Sinha (Marine Georesources & Geotechnology, 2026)

sCentInDB: a database of essential oil chemical profiles of Indian medicinal plants - Shanmuga Priya Baskaran; Geetha Ranganathan; Ajaya Kumar Sahoo; Kishan Kumar; Jayalakshmi Amaresan; Kundhanathan Ramesh; R. P. Vivek-Ananth; Areejit Samal (Molecular Diversity, 2026)
Essential oils are complex mixtures of volatile compounds produced by aromatic plants and widely used in personal care, food flavoring, and pharmaceutical industry due to their odor and therapeutic properties. As a high-value and low-volume organic product, optimizing plant yield and modifying composition by leveraging knowledge on chemical profiles of essential oils can lead to enhanced bioproducts. Additionally, overharvesting of wild medicinal plants, especially in India, threatens biodiversity. Essential oil profiles of such plants can help regulate their exploitation. Here, we present sCentInDB, a manually curated FAIR-compliant DataBase of Essential oil Chemical profiles of Medicinal plants of India, compiled from published literature. sCentInDB contains data on 554 Indian medicinal plants at the plant part level, encompassing 2170 essential oil profiles, 3420 chemicals, 471 plant-part-therapeutic use associations, 120 plant-part-odor associations, and 218 plant-part-color associations. sCentInDB also compiles metadata such as sample location, isolation, and analysis methods. Subsequently, an extensive analysis of the chemical space in sCentInDB was performed. By constructing a chemical similarity network, terpenoids were found to be distributed across the network, indicating greater structural diversity. Moreover, a comparison of the scaffold diversity of chemicals in sCentInDB was performed against three other aroma libraries using cyclic system retrieval curves. Altogether, sCentInDB will serve as a valuable resource for researchers working on plant volatiles and employing genetic engineering to enhance oil yield and composition. Further, sCentInDB will aid in the establishment of quality standards for essential oils and provide vital insights for therapeutic and perfumery applications. sCentInDB is accessible at https://cb.imsc.res.in/scentindb/ . Graphical abstract Graphical abstract summarizing the workflow for constructing the sCentInDB database and analysis of the associated chemical space.

Revolutionizing energy storage: Self-charging supercapacitors toward self-powered micro and nano systems - Kaliyannan Manojkumar; Mukilan Muthuramalingam; Arunmetha Sundamoorthy; P S Srinivasa Babu; Rayavarapu Vamsi; Jananipriya Boominathan; Siddabattula Geetha Sri Priyanka; Sugato Hajra; Swati Panda; Hoe Joon Kim; Deepak Dubal; Venkateswaran Vivekananthan (Chemical Engineering Journal, 2025)

Aquaculture of Asian seabass (Lates calcarifer) in India: A comparative economic analysis across production systems and regions - Geetha R.; Abhinaya D.; Naffees Gowsar S. R.; Ravisankar T.; Kailasam M.; Jayakumar R.; Subburaj R.; Shinoj P.; Rajni Jain; Lal K. K.; Patil P. K. (Aquaculture International, 2025)

Genetic diversity, morphological variation and biochemical profiling of dolichos bean: a study for crop improvement - Krishnan Deepana; K. Geetha; P. Jeyaprakash; M. Sangeetha; K. Govindan; M. S. Aneesa Rani; S. Srividhya (Genetic Resources and Crop Evolution, 2025)

Molecular detection and serotyping of acute bacterial meningitis pathogens in Indian children - Geetha Nagaraj; Vandana Govindan; C. P. Girish Kumar; Shally Awasthi; Bimal Kumar Das; Hitender Gautam; Debasis Biswas; S. Ezhilarasi; S. Nivedhana; Ashish Bavdekar; Ravikumar Kadahalli Lingegowda (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Correction to: Integrating solid stem and multiple disease resistance for developing climate-resilient wheat (Triticum aestivum L.) - P. Shajitha; R. Nisha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; K. Gajalakshmi; Niharikha Mallick; Prashanth Babu; Rajbir Yadav; S. Vijaishree; K. Akileshwaran; John Peter; et al. (Cereal Research Communications, 2025)

Integrating solid stem and multiple disease resistance for developing climate-resilient wheat (Triticum aestivum L.) - P. Shajitha; R. Nisha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; K. Gajalakshmi; Niharikha Mallick; Prashanth Babu; Rajbir Yadav; S. Vijaishree; K. Akileshwaran; John Peter; et al. (Cereal Research Communications, 2025)

Cisgenics–An advanced breeding technique for Fruit crop amelioration - V. Boomika; M. S. Aneesa Rani; K. S. Vijai Selvaraj; P. Irene Vethamoni; R. Kalaiyarasi; P. Geetha (Euphytica, 2025)

MTV19ANet: A Multi-tier Visual Geometry Group 19 with Attention Network-Based Streamflow Prediction System - Shashank A; Geetha P; Jyothish Lal G; Sankaran Rajendran (Water Resources Management, 2025)

Management of Diverse Weed Flora in Widely Spaced Sugarcane Plant Crop in Tropical India Through Sequential and Tank Mix Application of Herbicides - S. Anusha; P. Geetha; V. Krishnapriya; A. S. Tayade; R. Arun Kumar (Sugar Tech, 2025)

The Aegilops ventricosa derived 2NvS translocation for enhanced defense against multiple diseases in wheat - R. Nisha; P. Shajitha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; Shailendra Jha; Niharika Mallick; Rajbir Yadav; S. C. Bhardwaj; O. P. Gangwar; S. Vijaishree; M. Geetha; et al. (Journal of Crop Science and Biotechnology, 2025)

Flood Susceptibility Map of Periyar River Basin Using Geo-spatial Technology and Machine Learning Approach - Sreekala S; P. Geetha; Dhanya Madhu (Remote Sensing in Earth Systems Sciences, 2025)

Exploring Withanolides from Withania somnifera: A Promising Avenue for Alzheimer’s Disease Treatment - Chitikela P Pullaiah; Preethi Priyadharshini SP; Phareedha SK; Yamini Nemalapalli; Geetha Birudala; S Lahari; Shanmugam Vippamakula; R Shakila; Muni Swamy Ganjayi; Raghavendra Mitta (Current Pharmacology Reports, 2025)

The Dolichos bean: a versatile legume with potential to address food security challenges and strategies for improvement - Krishnan Deepana; K. Geetha; P. Jeyaprakash; M. Sangeetha; K. Govindan (Genetic Resources and Crop Evolution, 2025)

Advanced landslide susceptibility mapping and analysis of driving mechanisms using ensemble machine learning models - Mashael Maashi; Nada Alzaben; Noha Negm; V. Venkatesan; S. Sabarunisha Begum; P. Geetha (Journal of South American Earth Sciences, 2025)

Effects of Metarhizium anisopliae on the histochemistry and enzymatic activities of Helicoverpa armigera (Hübner, 1809) - Yamini R; Shanmugam P.S; Murugan M; Geetha N; Meenakshi P; Srinivasan T; Premalatha K; Kandan A; Sathiyaraj G; Vivekanandhan P (Biocatalysis and Agricultural Biotechnology, 2024)

Digital assessment of post-harvest Nendran banana for faster grading: CNN-based ripeness classification model - P.L. Arunima; Pratheesh P. Gopinath; P.R. Geetha Lekshmi; M. Esakkimuthu (Postharvest Biology and Technology, 2024)

Comprehensive river water quality monitoring using convolutional neural networks and gated recurrent units: A case study along the Vaigai River - Geetha T. S; Gandhimathi G; Chellaswamy C; Thiruvalar Selvan P (Journal of Environmental Management, 2024)

Growth trends during life stages in the Arabian Sea middle-sized form Sthenoteuthis oualaniensis (Cephalopoda: Ommastrephidae) from the Western Indian Ocean - Nadakkal Ragesh; Kurichithara K. Sajikumar; Geetha Sasikumar; K. P. Said Koya; Kolliyil S. Mohamed (Molluscan Research, 2024)

Validation, dissipation kinetics and monitoring of flonicamid and dinotefuran residues in paddy grain, straw, its processed produces and bran oil using LC-MS/MS - Ashok Kumar Karedla; R. Surya Raj; S.V. Krishnamoorthy; A. Suganthi; K. Bhuvaneswari; S. Karthikeyan; P. Geetha; M. Senthilkumar; S. Jeyarajan Nelson (Food Chemistry, 2024)

Resolving taxonomic ambiguity and distribution of Tremoctopus gracilis (Cephalopoda: Tremoctopodidae) based on molecular evidence - Kurichithara K. Sajikumar; Geetha Sasikumar; Divya Viswambharan; Summaya Rahuman; N. S. Jeena; Nedumpally Vineesh; C. P. Binesh; K. P. Said Koya; V. Mahesh; Prathibha Rohit; P. K. Asokan; Smruthu Mohan; et al. (Marine Biology, 2024)

Development of analytical method for simultaneous determination of chlorantraniliprole and fipronil residues in Moringa leaf using LC–MS/MS and decontamination of Moringa leaves using household reagents - Rohit Ramesh; K. Bhuvaneswari; A. Suganthi; P. Geetha; S. Haripriya (South African Journal of Botany, 2023)

In silico identification of potential inhibitors of vital monkeypox virus proteins from FDA approved drugs - Ajaya Kumar Sahoo; Priya Dharshini Augusthian; Ishwarya Muralitharan; R. P. Vivek-Ananth; Kishan Kumar; Gaurav Kumar; Geetha Ranganathan; Areejit Samal (Molecular Diversity, 2023)

Twisted top disease a destructive disease of sugarcane in India - R. Viswanathan; N. Geetha; K. P. Salin; R. Selvakumar; P. Malathi; A. R. Sundar; R. Nithyanantham; K. Manivannan (Indian Phytopathology, 2023)

Resource Use Efficiency and Yield Advantage of Sugarcane-Based Cropping System in Tropical India - P. Geetha; A. S. Tayade (Sugar Tech, 2023)

Development of in vitro pollen germination protocol for recalcitrant triticale pollen (X Triticosecale Wittmack) - P. Jayaprakash; John Peter; P. Shajitha; V. Balaji; R. Nisha; M. Geetha; V. K. Vikas; M. Sivasamy (Cereal Research Communications, 2023)

Transcription factors controlling the expression of oxidative stress associated genes in rice (Oryza sativa L.) - D. Sujitha; H. G. Jalendra Kumar; Garima Thapliayal; Garima Pal; P. A. Vanitha; Akshay Uttarkar; Mahesh Patil; B. H. Rajashekar Reddy; Vidya Niranjan; Usha Rayalcheruvu; Geetha Govind; M. Udayakumar; et al. (Plant Biotechnology Reports, 2023)

Neuroprotective effect of Hydrocotyle sibthorpioides against monosodium glutamate-induced excitotoxicity - Iswar Hazarika; Geetha Kannoth Mukundan; P. Sivakami Sundari (Natural Product Research, 2022)

Correction to: Adult plant stem rust resistance in durum wheat Glossy Huguenot: mapping, marker development and validation - Rohit Mago; Chunhong Chen; Xiaodi Xia; Alex Whan; Kerrie Forrest; Bhoja R. Basnet; Geetha Perera; Sutha Chandramohan; Mandeep Randhawa; Matthew Hayden; Urmil Bansal; Julio Huerta‑Espino; et al. (Theoretical and Applied Genetics, 2022)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Adult plant stem rust resistance in durum wheat Glossy Huguenot: mapping, marker development and validation - Rohit Mago; Chunhong Chen; Xiaodi Xia; Alex Whan; Kerrie Forrest; Bhoja R. Basnet; Geetha Perera; Sutha Chandramohan; Mandeep Randhawa; Matthew Hayden; Urmil Bansal; Julio Huerta-Espino; et al. (Theoretical and Applied Genetics, 2022)

Epidemiology of sugarcane wilt: predisposition by root borer Polyocha depresella a myth or reality - R. Viswanathan; R. Selvakumar; N. Geetha; C. G. Balaji; A. Annadurai; Adhini S. Pazhani; P. Malathi; A. Ramesh Sundar; R. Nithiyanantham; K. Manivannan (Indian Phytopathology, 2022)

The modulatory effect of Hydrocotyle sibthorpioides in attenuating the aluminium chloride induced neurotoxicity in rat brain - Iswar Hazarika; Geetha Kannoth Mukundan; Sivakami P. Sundari; Anju Das (Advances in Traditional Medicine, 2022)

Techno-economic evaluation of Asian seabass (Lates calcarifer) nursery rearing in small net cages (hapas) under different coastal salinities - M. Kumaran; K. P. Kumaraguru Vasagam; R. Subburaj; P. R. Anand; K. Ramachandran; R. Geetha; D. Deboral Vimala; R. Anandaraja; M. Jayanthi; C. V. Sairam (Aquaculture International, 2022)

Standardizing Planting Agro-techniques for Sugarcane Tissue Culture Plantlets and Bud Chip Settlings - A. S. Tayade; P. Geetha; S. Anusha (Sugar Tech, 2021)

Role of physical oceanography parameters in ocean’s biological response with the passage of cyclone Titli in the Bay of Bengal - K Vijay Prakash; Ch S Geetha Vimala; P V Nagamani; N K Baranval; Shivashankar Manche; T Preethi Latha; I V G Bhavani; Y Umamaheswara Rao; Ch S N Phanindra; K Srinivas; K P Kumari (Journal of Earth System Science, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Assessment of Water Quality Along the Southeast Coast of India During COVID-19 Lockdown - K. Vijay Prakash; Ch. S. Geetha Vimala; T. Preethi Latha; Chiranjivi Jayaram; P. V. Nagamani; Ch. N. V. Laxmi (Frontiers in Marine Science, 2021)
The COVID-19 pandemic has affected the entire world and has had a devastating impact on both lives and livelihoods in India. The only way to defeat the rapid spread of COVID-19, is to shut down socio-economic activities and to maintain minimal human interaction with the implementation of a lockdown. Such lockdowns have manifested in a pollution curtailment in almost all spheres of the planet, including in marine pollution. Quantifying this decrease in pollution levels enables the scientific community to assess the contribution of anthropogenic (especially non-essential) activities to global/regional pollution levels. This paper aims to study the impact of the stringent lockdown period (phase 1 and 2) on coastal water quality along the Chennai coast of India, by analyzing suspended matter concentration (SPM), a key element of water quality and diffuse attenuation coefficient, K d (490), using LANDSAT-8 Operational Land Imager (OLI) data. LANDSAT-8/OLI, L1TP scenes were subjected to radiometric calibration and atmospheric correction to derive surface reflectance values from raw digital numbers using ACOLITE software and a brief insight has been given for the Dark Spectrum Fitting algorithm used in ACOLITE. SPM concentration decreased by 15.48 and 37.50% in the Chennai and Ennore ports, respectively, due to minimal vessel movement and cargo handling. The stringent lockdown led to the operation of fewer thermal plant units, thus less fly ash was emanated, resulting in a 28.05% reduction in SPM levels over Ennore creek. As industrial and commercial activities subsided, the city’s water bodies became clearer than they were just a fortnight prior to the lockdown, with a reduction of 22.26% of SPM in Adyar and 33.97% in Cooum riverine estuaries. Decrease in K d (490) showed a positive relationship with SPM and thus improved coastal water quality because of the reduction of SPM during this period. The variations in PM2.5 and PM10 concentrations were studied using National Air Quality Monitoring Programme (NAMP) data and reduced levels in particulate matter concentration (PM2.5 and PM10) for the Adyar residential area (24.38 and 28.43%) and for the Nungampakkam commercial area (36.09 and 67.18%) were observed. A significant reduction in PM2.5 concentration (45.63%) was observed in the Ennore-Manali Industrial region.

Additive main effects and multiplicative interaction analyses of yield performance in rice genotypes for general and specific adaptation to salt stress in locations in India - S. L. Krishnamurthy; P. C. Sharma; D. K. Sharma; Y. P. Singh; V. K. Mishra; D. Burman; B. Maji; S. Mandal; S. K. Sarangi; R. K. Gautam; P. K. Singh; K. K. Manohara; et al. (Euphytica, 2021)
The aim of this study was to identify stable rice genotypes tolerant to a salt stress environment and to identify ideal mega-environments using AMMI (additive main effects and multiplicative interaction) stability model analysis. A total of 13 rice genotypes and three salt tolerance checks were evaluated across 13 salt stress locations (alkaline and saline) for the two kharif seasons of 2014 and 2015. Genotype CSR 36 (CHK3) was found to be the most ideal of those tested. Genotypes CHK2 (CST 27) and IR 87952-1-1-1-2-3-B (G05) were found to be the most stable, with above average yields. The check CSR 36 (CHK3) genotype was the best performer in the majority of the environments studied, followed by CSR 27 (CHK2) and IR 87952-1-1-1-2-3-B (G05) which were the best genotypes in the mega-environment consisting of 21 environments evaluated across stress locations and year combinations. Overall, the most promising genotype (IR 87952-1-1-1-2-3-B) had high mean yield and stability and could be used for commercial cultivation or used as donor for breeding programs across salt-affected soils. The genotypes GN13 (IR 87938-1-1-2-1-3-B) and GN11 (IR 87938-1-2-2-1-3-B) showed 60–80% yield advantage at specific salt stress locations, showing that these genotypes could be used for specific environments of salt-affected soils in India.

RECK and TIMP-2 mediate inhibition of MMP-2 and MMP-9 by Annona muricata - G Drishya; Jyotsna Nambiar; Sanu K Shaji; Muralidharan Vanuopadath; A Achuthan; Abishek Kumar; Ashna Alias; Ayesha Sherif; Catherine Joseph; P Divya; Damu Sunil Kumar; Chinchu Bose; et al. (Journal of Biosciences, 2020)

Leukocyte segmentation in peripheral blood images using a novel edge strength cue-based location detection method - K. Sudha; P. Geetha (Medical & Biological Engineering & Computing, 2020)

Trends, causes, and indices of import rejections in international shrimp trade with special reference to India: a 15-year longitudinal analysis - R. Geetha; T. Ravisankar; P. K. Patil; Satheesha Avunje; S. Vinoth; C. V. Sairam; K. K. Vijayan (Aquaculture International, 2020)

Agronomic Response, Weed Smothering Efficiency and Economic Feasibility of Sugarcane and Legume Intercropping System in Tropical India - P. Geetha; A. S. Tayade; C. A. Chandrasekar; T. Selvan; Rajesh Kumar (Sugar Tech, 2019)

Characterization of inertia gravity waves and associated dynamics in the lower stratosphere over the Indian Antarctic station, Bharati (69.4°S, 76.2°E) during austral summers - N. Koushik; Karanam Kishore Kumar; K. V. Subrahmanyam; Geetha Ramkumar; I. A. Girach; M. Santosh; K. Nalini; M. Nazeer; P. R. Shreedevi (Climate Dynamics, 2019)

Bio-intensive Modulation of Sugarcane Ratoon Rhizosphere for Enhanced Soil Health and Sugarcane Productivity Under Tropical Indian Condition - A. S. Tayade; P. Geetha; S. Anusha; R. Dhanapal; K. Hari (Sugar Tech, 2019)

Efficient Water Management in Sugarcane with Composted Coir Pith and Sugarcane Trash Under Tropical Indian Conditions - R. Dhanapal; A. S. Tayade; A. Bhaskaran; P. Geetha (Sugar Tech, 2019)

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Range extension of a bathypelagic squid, Bathyteuthis bacidifera (Cephalopoda: Bathyteuthidae), to the south Arabian Sea with special reference to its age and growth pattern - K. K. Sajikumar; A. I. Arkhipkin; V. Venkatesan; K. M. Jestin Joy; C. P. Binesh; Geetha Sasikumar; Kolliyil S. Mohamed (Marine Biodiversity, 2018)

Phycomolecule-coated silver nanoparticles and seaweed extracts induced high-frequency somatic embryogenesis and plant regeneration from Gloriosa superba L. - D. Mahendran; P. B. Kavi Kishor; N. Geetha; P. Venkatachalam (Journal of Applied Phycology, 2018)

Immune Responses in Malaria Transmission - Geetha P. Bansal; Nirbhay Kumar (Current Clinical Microbiology Reports, 2018)

Inhibitory activity of bio-active compounds isolated from Anadara granosa in shrimp health management - D. Sunil Kumar; P. Janakiram; M. Murali Krishna Kumar; G. Krishna Geetha (World Journal of Microbiology and Biotechnology, 2017)

Impact of the Charge Ratio on the In Vivo Immunogenicity of Lipoplexes - Zahra Heidari; Jaspreet S. Arora; Dibyadyuti Datta; Vijay T. John; Nirbhay Kumar; Geetha P. Bansal (Pharmaceutical Research, 2017)

Plant-disperser mutualisms in a semi-arid habitat invaded by Lantana camara L. - Geetha Ramaswami; P. Somnath; Suhel Quader (Plant Ecology, 2017)

Effect of phycochemical coated silver nanocomplexes as novel growth-stimulating compounds for plant regeneration of Alternanthera sessilis L. - P. Venkatachalam; S. Malar; M. Thiyagarajan; P. Indiraarulselvi; N. Geetha (Journal of Applied Phycology, 2017)

Climate change projections for Tamil Nadu, India: deriving high-resolution climate data by a downscaling approach using PRECIS - Prasanta Kumar Bal; A. Ramachandran; R. Geetha; B. Bhaskaran; P. Thirumurugan; J. Indumathi; N. Jayanthi (Theoretical and Applied Climatology, 2016)

Potent Functional Immunogenicity of Plasmodium falciparum Transmission-Blocking Antigen (Pfs25) Delivered with Nanoemulsion and Porous Polymeric Nanoparticles - Rajesh Kumar; Grace Ledet; Richard Graves; Dibyadyuti Datta; Shana Robinson; Geetha P. Bansal; Tarun Mandal; Nirbhay Kumar (Pharmaceutical Research, 2015)

A maize α-zein promoter drives an endosperm-specific expression of transgene in rice - J. Beslin Joshi; S. Geetha; Birla Singh; K. K. Kumar; E. Kokiladevi; L. Arul; P. Balasubramanian; D. Sudhakar (Physiology and Molecular Biology of Plants, 2015)

Plasma anti-α-galactoside antibody binds to serine- and threonine-rich peptide sequence of apo(a) subunit in Lp(a) - M. Geetha; V. Kalaivani; P. S. Sabarinath; P. S. Appukuttan (Glycoconjugate Journal, 2014)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Plant regeneration and production of embelin from organogenic and embryogenic callus cultures of Embelia ribes Burm. f.—a vulnerable medicinal plant - A. V. Raghu; Kuzhiyumparambil Unnikrishnan; S. P. Geetha; Gerald Martin; Indira Balachandran (In Vitro Cellular & Developmental Biology - Plant, 2011)

Identification of RAPD markers linked to sex determination in guggal [Commiphora wightii (Arnott.)] Bhandari - Sanghamitra Samantaray; K. A. Geetha; K. P. Hidayath; Satyabrata Maiti (Plant Biotechnology Reports, 2010)

SCS-CN-based Continuous Simulation Model for Hydrologic Forecasting - K. Geetha; S. K. Mishra; T. I. Eldho; A. K. Rastogi; R. P. Pandey (Water Resources Management, 2008)

Involvement of silicon in pearl millet resistance to downy mildew disease and its interplay with cell wall proline/hydroxyproline-rich glycoproteins - S. Deepak; G. Manjunath; S. Manjula; S. Niranjan-Raj; N. P. Geetha; H. S. Shetty (Australasian Plant Pathology, 2008)

In vitro clonal propagation through mature nodes of Tinospora cordifolia (Willd.) Hook. F. & Thoms.: An important ayurvedic medicinal plant - A. V. Raghu; S. P. Geetha; Gerald Martin; Indira Balachandran; P. N. Ravindran (In Vitro Cellular & Developmental Biology - Plant, 2006)

Effects of presowing treatments, desiccation and storage conditions on germination of Strychnos nux-vomica seeds, a valuable medicinal plant - V. Sivakumar; R. Anandalakshmi; R. R. Warrier; M. Tigabu; P. C. Odén; S. N. Vijayachandran; S. Geetha; B. G. Singh (New Forests, 2006)

Monitoring Trace Metal Contaminants in Green Mussel, Perna viridis from the Coastal Waters of Karnataka, Southwest Coast of India - Geetha Sasikumar; P. K. Krishnakumar; G. S. Bhat (Archives of Environmental Contamination and Toxicology, 2006)

Biomarkers of environmental contaminants in field population of green mussel (Perna viridis) from Karnataka–Kerala coast (South West coast of India) - P. K. Krishnakumar; Geetha Sasikumar; G. S. Bhat; D. P. K. Asokan (Ecotoxicology, 2006)

Immunomodulatory effects of seabuckthorn (Hippophae rhamnoides L.) against chromium (VI) induced immunosuppression - S. Geetha; Vandana Singh; M. Sai Ram; G. Ilavazhagan; P. K. Banerjee; R. C. Sawhney (Molecular and Cellular Biochemistry, 2005)

Unsaturated fatty acids from zoospores of Sclerospora graminicola induce resistance in pearl millet - K. N. Amruthesh; N. P. Geetha; H. J. Lyngs Jørgensen; E. de Neergaard; H. Shekar Shetty (European Journal of Plant Pathology, 2005)

Hyaluronan is not elevated in urine or serum in Hutchinson-Gilford Progeria Syndrome - Leslie B. Gordon; Ingrid A. Harten; Anthony Calabro; Geetha Sugumaran; Antonei B. Csoka; W. Ted Brown; Vincent Hascall; Bryan P. Toole (Human Genetics, 2003)

Effect of lupeol and lupeol linoleate on lysosomal enzymes and collagen in adjuvant-induced arthritis in rats - T. Geetha; P. Maralakshmi (Molecular and Cellular Biochemistry, 1999)

A rapid protocol for somatic embryogenesis from immature leaflets of groundnut (Arachis hypogaea L.) - P. Venkatachalam; P. B. Kavi Kishor; N. Geetha; M. Thangavelu; N. Jayabalan (In Vitro Cellular & Developmental Biology - Plant, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

In Vitro selection of groundnut cell lines fromCercosporidium personatum culture filtrates and regeneration of resistant plants through cell culture - P. Venkatachalam; N. Geetha; N. Jayabalan; S. Saravanababu (Journal of Plant Biology, 1998)

Separation of bovine heart galactose lectin from endogenous glycoproteins co-purified with the lectin during affinity chromatography - P. S. Appukuttan; K. I. Annamma; M. Geetha; P. L. Jaison (Journal of Biosciences, 1998)

Antifungal fractions and compounds from uncrushed Green Leaves ofAzadirachta indica - G. Suresh; N. S. Narasimhan; S. Masilamani; P. D. Partho; Geetha Gopalakrishnan (Phytoparasitica, 1997)